البحوث النوعية في العصر الرقمي فعالية استخدام برامج تحليل البيانات النوعية بمساعدة الحاسوب في دراسة بيانات شبكات التواصل الاجتماعي. - طيفور فاطمة (Hakika (The Truth) Journal for Social & Human Sciences, 2025)
The Analysis of social networks encompasses a collection of technical tools that facilitate the modelling of social relationships, wherein the observable connections among network users are depicted through graphs that illustrate the degrees of density and strength among the various participants in the network. This study emphasizes both the programs that facilitate text manipulation and those that enable the analysis of audio-visual sources, as well as the creation of graphic representations of that analysis. In this paper, we therefore aim to demonstrate the use of CAQDAS, specifically Atlas.ti and NVivo, which provide the researcher in the field of media and communication sciences with the ability to encode data, create logical and contextual links between the generated categories, or verify the resulting hypotheses and then construct theories in social Media’s corpora analysis on one hand. On the other hand, we try to elucidate the main challenges that the researcher may face when using these programs. Whether, The technique of application, the precision of the data acquired, and the ethical considerations.